Basic bangla sign language recognition and sentence building using Microsoft Kinect - Ahmed, Khan Rafin; Mumu, Sabrin Momotaz; Shuvra, Fatema Tuz Zohora (BRAC University, 2018)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2017.